Direito antitruste: defesa da concorrência ou políticas econômicas? - Souza, Kelly Cristina Mendes (2006)
Based on bibliographic research, this paper used doctrines, legislations, case laws, as well as information transmitted by several sources, aiming to identify the real purpose of the antitrust law in the Brazilian economic system. Therefore, it started with analyses of the Brazilian economic order, because the antitrust law makes part of this economic order. Furthermore, the antitrust law was studied, by analyzing several unfair trade practices, such as unfair competition, abuse of economic power, cartels, dumping and predatory pricing. International antitrust law, as well as the relevant market and the national legislation competition matters were also mentioned. In the end, it was made a confrontation between the Brazilian legislation competition system and the national economic model, asking the purpose and the significance of the decisions of the antitrust authorities. The analysis of those considerations enables the interpretation of the Brazilian antitrust law and to identify its function in the Brazilian economic system.